Practical aspects of forecasting the company’s financial performance - V. V. Kookueva (Вестник университета, 2021)
Financial planning and forecasting are important functions of financial managers, analysts and are important in making management decisions. Long-term growth and strengthening of the company’s position in the market are impossible without high-quality financial planning. Improving the quality of forecasting requires a thorough analysis of the application of various methods and techniques. The article considers the methodological problems of forecasting key financial indicators related to forecasting the final results of the company. The algorithm for creating refined factor predictive models of financial indicators has been presented and tested. Based on the combined application of various economic and mathematical methods, the forecasting method has been improved, which makes it possible to reduce the forecast error, which in turn allows us making more accurate financial decisions.